PH evolution around the AZ31/Steel galvanic couple under gelled-electrolytes: A numerical and experimental study. (January 2021) - Ortiz-Ozuna, A.; Godínez, F.A.; Ramírez-Barat, B.; Garcia-Alonso, M.C.; Escudero, M.L.; Fajardo, S.; Genesca, J.; Montoya, R.
Abstract: This work presents an experimentally validated theoretical model for Mg alloy dissolution that accounts for transport phenomena. The galvanic interaction between AZ31 Mg alloy and low carbon steels in a solid electrolyte was simulated. The use of a solid agar-based electrolyte allowed to neglect the strong convective effects that are normally present during Mg alloy dissolution caused by copious hydrogen evolution. Furthermore, it allowed for a constant electrolyte thickness to be fixed. The gelled-electrolyte contained a pH indicator to permit a reliable visual tracking of the transient propagation of H + and OH − ions during the electrochemical reaction.